Transcriptome Analysis of Chloris virgata, Which Shows the Fastest Germination and Growth in the Major Mongolian Grassland Plant - Bolortuya, Byambajav; Kawabata, Shintaro; Yamagami, Ayumi; Davaapurev, Bekh-Ochir; Takahashi, Fuminori; Inoue, Komaki; Kanatani, Asaka; Mochida, Keiichi; Kumazawa, Minoru; Ifuku, Kentaro; Jigjidsuren, Sodnomdarjaa; Battogtokh, Tugsjargal; et al. (Frontiers in Plant Science, 2021)
Plants in Mongolian grasslands are exposed to short, dry summers and long, cold winters. These plants should be prepared for fast germination and growth activity in response to the limited summer rainfall. Here, we identified the Chloris virgata Dornogovi accession as the fastest germinating plant in major Mongolian grassland plants. It germinated just 5 h after treatment for germination initiation and showed rapid growth, especially in its early and young development stages. This indicates its high growth potential compared to grass crops such as rice and wheat. By assessing growth recovery after animal bite treatment (mimicked by cutting the leaves with scissors), we found that C. virgata could rapidly regenerate leaves after being damaged, suggesting high regeneration potential against grazing. To analyze the regulatory mechanism involved in the high growth potential of C. virgata, we performed RNA-seq-based transcriptome analysis and illustrated a comprehensive gene expression map of the species. Through de novo transcriptome assembly with the RNA-seq reads from whole organ samples of C. virgata at the germination stage (2 days after germination, DAG), early-young development stage (8 DAG), young development stage (17 DAG), and adult development stage (28 DAG), we identified 21,589 unified transcripts (contigs) and found that 19,346 and 18,156 protein-coding transcripts were homologous to those in rice and Arabidopsis, respectively. The best-aligned sequences were annotated with gene ontology groups. When comparing the transcriptomes across developmental stages, we found an over-representation of genes involved in growth regulation in the early development stage in C. virgata. Plant development is tightly regulated by phytohormones such as brassinosteroids, gibberellic acid, abscisic acid, and strigolactones. Moreover, our transcriptome map demonstrated the expression profiles of orthologs involved in the biosynthesis of these phytohormones and their signaling networks. We discuss the possibility that C. virgata phytohormone signaling and biosynthesis genes regulate early germination and growth advantages. Comprehensive transcriptome information will provide a useful resource for gene discovery and facilitate a deeper understanding of the diversity of the regulatory systems that have evolved in C. virgata while adapting to severe environmental conditions.